The Development of Language Acceptance for Children Aged 0-5 Years in RT004/RW003 Jatimurni, Bekasi - Mulyani, Sri; Septiani, Eka; Indah Sari, Nur (Jurnal KATA, 2019)
The aim of study was to determine the development of language acquisition of children aged 0-5 years in RT004 / RW003 Jatimurni, Bekasi and find out the average length of speech of the  first language acquisition Zeen, Tyas, Putri, Fatih, Radit, and Kenzi. The research method uses qualitative description, while  the approach used is a longitudinal approach. The main features of  longitudinal require a long time because what is examined is the development of something being studied from one time to another. Source of data from language acquisition of children aged 0-5 years. The result of the development research on language acquisition of children aged  0-5 years in RT 004 / RW 003, Jatimurni, Bekasi is children aged 0-3 months wake up when they hear a loud voice, which is crying, if they  hear others talking they pay attention to the person, he smiles when invited to talk,can  recognize the voice of his cast or caretaker and stop crying when invited to talk. Paying attention to the eyes and mouth of  people who act as they speak, look for sound sources by moving their eyes and bodies,looking at objecta around them, and showing interest in objects that are in their environment, and using their environment and using their hand and mouth to explore their motor sensory, while Tyas age 1 the averages length of speech, which is 0.2. Putri age of 2.3 years of utterance averages, which is 0.43, Fatih age 3.4 years the average length of  speech, which is 0.60, Radit age of 4 years the average length of  speech, namely  1.6, and Kenzi age of 5 years the average length of  speech 2.15. So,, the development of children’s language acquisition will continue to increase according to the increase in age and cognitive development.